MANAGEMENT OF HANDLING SEPARATISM (ZULU TRIBE) IN SOUTH AFRICA, BENCHMARKING TO OVERCOME THE PAPUAN CONFLICT - Bayu Setiawan; Arifuddin Uksan; Ahmed Sukendro (International Journal of Social Science, 2023)
The South African government has succeeded in overcoming the problem of separatism in Zulu, but the Indonesian government still has to face the problem of separatism in Papua. This study aims to make the management of handling separatist movements in South Africa (Zulu Region) a benchmarking for decision makers. This research was conducted with a qualitative descriptive approach. The results of the research show that the root of the problem of separatism, namely the demand for autonomy rights for the Zulu Tribe, has been resolved through peaceful mean. On the other hand, the Government of Indonesia has also made a lot of efforts, in ways that are relatively exactly the same as those taken by the South African, but not yet fully successful. So that it becomes very relevant for the Indonesian government to carry out a thorough evaluation regarding the implementation of the policy of granting special autonomybased on the South African experience